Differential Source Count for Gamma-Ray Bursts - Banerjee, Shreya; Eichler, David; Guetta, Dafne (Astrophysical Journal, 2021)
Different forms of long gamma-ray burst (GRB) luminosity functions are considered on the basis of an explicit physical model. The inferred flux distributions are compared with the observed ones from two samples of GRBs, Swift and Fermi GBM. The best-fit parameters of the luminosity functions are found, and the physical interpretations are discussed. The results are consistent with the observation of a comparable number of flat-phase afterglows and monotonically decreasing ones.
CRIS-Team WoS Importer:2021-11-12